Pelaksanaan Komuniti Pembelajaran Profesional (KPP) untuk peningkatan kemahiran guru Bahasa Melayu mengajar penulisan karangan - Abu Bakar, Dima Mazlina @ Siti Aishah; Jamian, Abdul Rashid (Faculty of Education, University of Malaya, 2016)
This study aimed at examining the implementation of Professional Learning Communities (PLC) for upgrading the skills of Malay teachers teaching essay writing process, at a secondary school in the state of Kedah, Malaysia. The Teacher Training Division (Bahagian Pendidikan Guru -BPG) began to implement PLC to enhance the professionalism of teachers in 2011. The implementation of PLC in Malaysia involves teachers of Mathematics, English, Science and History. Teachers of other subjects are also encouraged to cultivate PLC communities. The findings indicate that the strategies implemented by the PLC managed to change the attitude and teaching of teachers involved in the study, especially in the teaching and learning of essay writing. The findings also show that teachers should always seek alternatives to improve teaching methods and share best practices among themselves. Thus, PLC can be a platform for building pedagogical knowledge of teachers as it enables teachers to always learn and gain knowledge to improve their classroom teaching methods.